UPAYA MEWUJUDKAN DYNAMIC MANAGERIAL DALAM MEMAKSIMALKAN PELAYANAN PUBLIK: STUDI PADA KANTOR JENDERAL KEKAYAAN NEGARA JAWA TIMUR - Mohammad Chifni; Kuswandi Kuswandi; Sri Rahayu (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to explore efforts that can be made to realize dynamic management (dynamic managerial) in order to maximize public services. The focus of this study is the Office of the General of State Assets in East Java as a case study. The research methods used include interviews, observation, and document analysis to collect qualitative data. This research identifies several key factors that influence managerial dynamics in the context of public services, including internal and external factors. Internal factors include competency and capacity of human resources, responsive organizational structure, and use of information technology. On the other hand, external factors include the dynamics of public policy, community expectations, and changes in the external environment. Research findings show that the application of dynamic management can increase the efficiency and effectiveness of public services. Strategies that include increasing human resource capacity, structural termination, and utilizing information technology can have a positive impact in increasing responsiveness to community demands. It is hoped that the results of this research can contribute to the development of dynamic management concepts in the context of public services, especially within the Office of the General of State Assets in East Java. The practical implication is that the application of dynamic management practices can be a basis for improving the performance and quality of public services, as well as providing guidance for similar agencies in facing dynamic changes in the future.